Sosialisasi Penerapan Pemasaran Digital Pada Cafe Uni - Zulstra, Jumadil Dwi; Dianti, Muthia Rahma; Dianti, Hamidah Rahim (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Community Service is a form of the Tridharma of Higher Education. This program is proposed to carry out activities that are socialized to cafe partners in the city of Padang. This community service is made with the aim of increasing the knowledge and skills of Cafe Owners in maximizing digital marketing that is more effective and efficient. The service method used is in the form of socialization. The training stages are divided into 4 (four) stages, namely the preparation stage, the implementation stage, the program evaluation stage, and the reporting stage. The benefits of this PKM program were felt by partners who were initially ignorant of technology, and after socializing the partners' knowledge increased about the importance of digital marketing for business development.